Analysis of Al-Arabiyah Lil-Hayah Volume I Teaching Materials - Narul Hasyim Muzadi; Mawadda Warahmah; Muh. Thahilal jahidul Hasyb; Shofil Fikri (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Teaching materials are a fundamental element in education, especially in Arabic teaching which has distinctive linguistic and cultural characteristics, so its development must be in line with the needs of effective learning. This study aims to describe the development of Al-Arabiyah Lil-Hayah Volume I teaching materials at PKPBA UIN Maulana Malik Ibrahim Malang based on aspects of: a) relevance to the curriculum, b) systematic material structure, c) appropriate language presentation, d) interesting and interactive, e) paying attention to psychological aspects and individualization, f) completeness of components, and g) oriented to evaluation and reflection. This research used a qualitative method with a case study. Data were collected through interviews, observation, and documentation analysis, then analyzed using the Miles and Huberman model. The results showed that this teaching material is relevant to the curriculum and academic and social needs. The materials are organized systematically, use Fusha Arabic for formal communication, and are equipped with the HATI application for access to additional materials. The design is attractive and interactive with illustrations and digital exercises. These teaching materials also pay attention to individual needs through material differentiation and have structured components such as learning objectives, instructions, and evaluation based on contextual and digital questions. Overall, these teaching materials are innovative and effective in improving Arabic learning.